Análise dinâmica de rotores em balanço utilizando procedimentos computacionais e experimentais - Raimundo Eduardo Cota (2008)
This work deals with a study of the dynamic behavior of overhung rotors running below the first critical speed, which are supported by roller bearings. A special case of overhung rotor, which consists of an industrial blower for reheating furnace, is selected for this study. The selected rotor is supported on roller bearings, which are mounted on metallic base installed on a concrete foundation. Some important dynamic aspects of the overhung rotor behavior are analyzed by using both analytical-experimental and computational procedures. The experimental study is performed on a blower rotor, which has been used to feed combustion ir into industrials furnace, that rotates at 1,800 rpm. The rotor is driven by an electrical motor of 150 hp, and has the blowing capacity of 11,300 Nm3/h at pressure of 850 mmH2O and temperature of 250º C. Bump tests and constant speed vibration tests are performed on this rotor at several operating conditions, rendering the frequency spectraand the Bode diagrams associated with the rotating system vibratory response. Moreover, a computational procedure based on the finite element method is implemented to estimate the natural frequencies of overhung rotors supported on elastic bearings. The Campbell diagram is employed to compute the rotor critical speeds. The finite element modeling includes the blower impeller elastic flexibility, which has a strong influence on the dynamic response of the rotating system. The numerical results rendered in this work show that the impeller gyroscopic moments and flexibility dominate the blower rotor dynamic response in the speed range near the first critical speed.